PRP8 intein in dermatophytes: Evolution and species identification - Garces, Hans Garcia; Cordeiro, Raquel Theodoro; Bagagli, E. (Oxford Univ Press, 2018)
Dermatophytes are keratinophilic fungi belonging to the family Arthrodermataceae. Despite having a monophyletic origin, its systematics has always been complex and controversial. Sequencing of nuclear ribosomal ITS and D1/D2 rDNA has been proposed as an efficient tool for identifying species in this group of fungi, while multilocus analyses have been used for phylogenetic species recognition. However, the search for new markers, with sequence and size variation, which enable species identification in only one polymerase chain reaction (PCR) step, is very attractive. Inteins seems to fulfill these characteristics. They are self-splicing genetic elements present within housekeeping coding genes, such as PRP8, that codify the most important protein of the spliceosome. The PRP8 intein has been described for Microsporum canis in databases but has not been studied in dermatophytes in any other published work. Thus, our aim was to determine the potential of this intervening element for establishing phylogenetic relationships among dermatophytes and for identifying species. It was found that all studied species have a full-length PRP8 intein with a Homing Endonuclease belonging to the family LAGLIDADG. Phylogenetic analyses were consistent with other previous phylogenies, confirming Epidermophyton floccosum in the same Glade of the Arthroderma gypseum complex, Microsporum audouinii close to M. canis, differentiating A. gypseum from Arthroderma incurvatum, and in addition, better defining the Trichophyton interdigitale and Trichophyton rubrum species grouping. Length polymorphism in the HE region enables identification of the most relevant Microsporum species by a simple PCR-electrophoresis assay. Intein PRP8 within dermatophytes is a powerful additional tool for identifying and systematizing dermatophytes.
Keywords: dermatophytes; PRP8 intein; phylogeny; identification